(untitled) (Research, Society and Development, 2021)
The trajectory of Brazilian history portrays the experience of socioeconomic problems, capable of compromising the management and performance of municipalities, States and the Union. In this respect, the indicators exist in order to assess the degree of commitment of managers, effectively contributing to demonstrate the results of their actions to the communities. This article aims to analyze the Municipal Management Challenges Index and the allocation of resources in some strategic government functions in the capitals of the Northeast region in 2018. For this purpose, this research corresponds to a quantitative, documentary and exploratory study, using descriptive statistics, where the data were obtained through the Brazilian Finance database (FINBRA) released by the National Treasury Secretariat (STN) and the MACROPLAN website. The results show that among the cities surveyed Fortaleza, João Pessoa, Teresina and Recife present the best indicators. The worst indicators were from Maceió and Aracajú. As suggestions for future research it is hoped that you can continue the investigation over the years, as well as verify regional differences, demographic variables, political and economic representation.